Nevropatska komponenta pri kronični bolečini v križu - Zaletel, Marjan (Rehabilitacija (Ljubljana), 2010)
Chronic low back pain is highly prevalent in Western countries. Large epidemiological studies show that 20% to 35% of patients with back pain sufferfrom a neuropathic pain component. Presently, chronic lumbar radicular pain is the most common neuropathic pain syndrome. The pathophysiology of backpain is complex and nociceptive, and neuropathic pain-generating mechanisms are thought to be involved, which established the term mixed pain syndrome. Neuropathic pain may be caused by lesions of nociceptive sprouts within the degenerated disc, mechanical compression of the nerve root, or by action of inflammatory mediators originating from the degenerative disc even without any mechanical compression. Its diagnosis and management remain an enigma, mainly because there is no gold standard for either. Accuracy of diagnostic tests used to identify the source of back pain and their usefulnessin clinical practice, particularly for guiding treatment selection, is unclear. In connection with the specific instance of back pain (one of the single most costly disorders in many industrialized nations), neuropathic paincomponents are a significant cost factor.
Keywords: bolečina; Diagnosis; diagnostika; hrbtenica; Križ, bolečina; Low Back Pain; Neuralgia; Nevralgija; nevropatije; nevropatska bolečina